A view on certain conditions for economic growth in Bulgaria (2008–2013) - Penka Shishmanova (Managerial Economics)
Economic growth is a function of numerous factors that, in their totality, determine its dynamics and stability. This article views only those factors that, to the greatest extent, present the capacity of Bulgaria’s economy – labor resources, capital, and knowledge (education, innovations, information and communication technology). Their dynamics for the last ﬁve-year period outlines primarily unfavorable changes, which have had a limiting impact on economic growth. This also determines the challenges which Bulgaria has faced in recent years, as it has to direct its efforts towards increasing the effectiveness in the use of available resources.